"Is it pyrite, or a shed?": intricacies of induced polarisation surveying near grounded metallic infrastructure. Issue 1 (1st December 2019) - Neroni, Regis; Corbett, Sam
Summary: Metallic grounded infrastructure commonly found in built-up areas such as fences, sheds and various dwellings, can produce induced polarisation anomalies often indistinguishable from bedrock responses typically targeted by base and precious metals explorers. Unintended presence of measurements that have been affected by such cultural causative sources in input datasets for inverse modelling can lead to misleading resulting models and compromised exploration performance. Circumvention of anticipated cultural interference during data acquisition cannot always be guaranteed in built-up areas due to the often-inevitable density of grounded infrastructure and limited land access. Instead, survey design should be optimised to deliberately collect data affected by cultural contribution in order to facilitate accurate interpretation of anthropogenic responses in resulting inverted models. After demonstrating the threat of unmindful induced polarisation surveying near grounded metallic infrastructure, we present the results from an unprecedented optimised time-domain 3DIP dataset using trilinear multi-dipole arrays, which is trusted to enable the confident discrimination of undesirable surficial anomalies from features deemed worthy of follow-up investigations despite patchy land access.